An evaluation of osteoarthrosis in specific anatomic locations of the canine stifle joint treated with tibial plateau leveling osteotomy and tibial tuberosity advancement - S. Pinna; C. Tassani (The Veterinary Journal, 2026)

A new catfish species of Microcambeva Costa & Bockmann, 1994 ( S iluriformes: T richomycteridae) from southern Brazil, with a redescription of M. ribeirae Costa, Lima & Bizerril, 2004 - Lucas S. de Medeiros; Igor C. A. Souto‐Santos; Paulo A. Buckup; Juliano Ferrer; Vinicius J. C. Reis; Mario de Pinna; Sergio M. Q. Lima (Journal of Fish Biology, 2026)
Among the few species of Microcambeva reported as occurring in more than one hydrographic basin, M. ribeirae has been previously listed from both the Ribeira de Iguape and the Guaraqueçaba basins. However, morphological and molecular analyses revealed that the specimens from Guaraqueçaba represent a new species, which is described in this study. Therefore, the distribution of M . ribeirae is restricted to the Ribeira de Iguape basin, and this taxon is redescribed. The new species is the southernmost record of the genus and is diagnosed among congeners by the T‐shaped dark blotch in the dorsal portion of the head in preserved specimens. It is distinguished from most congeners, except for M. bendego and M. ribeirae , by the lack of a filamentous first pectoral‐fin ray. Distinguished from the latter species by having only five pre‐caudal vertebrae, the tip of the hyomandibula reaching the vertical through the anterior tip of the preopercle, and the last anal‐fin ray branched. Molecular analysis of the cytochrome c oxidase subunit I ( cox1 ) mitochondrial gene including most species of Microcambeva (except M. draco ) supports the close relationship of the new species with M. ribeirae . The two species are nonetheless genetically different, with a 2.2% molecular distance. The conservation status and biogeography of the new species and of M. ribeirae are discussed.

Asymmetries challenging global biodiversity sciences - Leandro O. Salles; Hussam Zaher; Marcos Tavares; Mario C. C. de Pinna; Rosane G. Collevatti; Krister T. Smith; Diego Pol; Hongyu Yi; Nancy B. Simmons; Christopher J. Tribe; Joaquin Arroyo-Cabrales; Nour-Eddine Jalil; et al. (Systematics and Biodiversity, 2026)

Application of droplet digital PCR for the detection of fish DNA in food products - S. Cau; B. Soro; R. Melillo; G. Piras; S. Salza; T. Tedde; F. Pinna; B. Vodret; C. Spanu (Food Research International, 2025)

How does cruciate ligament rupture treatment affect range of motion in dogs? - S. Pinna; M. Di Benedetto; C. Tassani (The Veterinary Journal, 2024)

Nutritional management of hyperlipaemia in a jenny: a brief report - S. Morrone; S. Sechi; C. Carta; A. Senes; R. Cocco; M. L. Pinna Parpaglia; E. Sanna Passino; M. G. Cappai (Veterinary Research Communications, 2024)
An adult jenny (5-years-old, non-pregnant) was presented to the Veterinary Teaching Hospital (VTH) of the University of Sassari, with a recent history of appetite loss, extreme underweight condition and reluctance to move. On physical inspection, emaciation [body condition score, BCS: 3/9], muscular waste [muscular condition score, MCS: 1/5], loose/running faeces [faecal score, FS: 2/8], and a general state of mild dehydration were found. Blood analyses outlined a general undernourishment condition [circulating albumins, ALB: 17.6 g/L (21.6–31.6 g/L)] with underlying systemic inflammatory profile and moderate increase in circulating enzymes to explore liver function [aspartate amino-transferase, AST: 657 u/L (279–430 u/L); alanine amino-transferase ALT: 60 u/L (5–14 u/L); gamma-glutamyl-transferase, γ-GT: 87 IU/L (14–69 IU/L); total bilirubin close to the upper limit, TB: 0.20 mg/dL(0.07–0.21 mg/dL)]and hyperlipaemia [TG: 8.70 mmol/L (0.60–2.87 mmol/L)], following fat depots mobilisation, with total cholesterol closed to the lower limit of the physiological range. Hyper-phosphataemia was linked to haemolytic anaemia [P:1.81 mmol/L (0.77–1.39 mmol/L) and red blood cells, RBC: 4.14 10 12 /L (4.40–7.10 10 12 )] aligned with the TB to the upper limit. On ultrasound abdominal imaging, enlarged and hyper-echogenic liver was observed. Based on the clinical evaluation, a condition of hepatic lipidosis was diagnosed, requiring dedicated nutritional treatment to solve the extreme emaciation along with the metabolic disorder in support of medical therapy. A two-step feeding protocol was planned to support treatments aiming at immediate re-hydration (Ringer lactate solution 2 ml/kg/8 h). The nutritional objectives were meant at first to restart the voluntary feed intake. Gradual increasing energy provision through a palatable hay-based diet was planned to cover one fourth of daily metabolizable energy requirement calculated on the expected metabolic weight, adjusted according to the daily intake of feed and clinical condition. At the conclusion of this first 7-day phase, circulating blood parameters were closer to the reference values and the BCS moved from 3 to 4 out of 9. Bowel motility was restored, and faecal score improved (4/8). In the second phase, allowance to pasture and a combination diet with compound mixed feed were designed. Within four weeks of starting the nutritional plan, blood parameters were re-established to reference values. The gradual feed provision calculated in this two-phase approach proved successful in support of the overall clinical improvement observed after four weeks of treatment, in a severely undernourished jenny with compromised liver functions.

Neuroimaging evaluations of olfactory, gustatory, and neurological deficits in patients with long-term sequelae of COVID-19 - Carla Masala; Michele Porcu; Gianni Orofino; Giovanni Defazio; Ilenia Pinna; Paolo Solla; Tommaso Ercoli; Jasjit S. Suri; Giacomo Spinato; Luca Saba (Brain Imaging and Behavior, 2024)
The World Health Organization indicated that around 36 million of patients in the European Region showed long COVID associated with olfactory and gustatory deficits. The precise mechanism underlying long COVID clinical manifestations is still debated. The aim of this study was to evaluate potential correlations between odor threshold, odor discrimination, odor identification, and the activation of specific brain areas in patients after COVID-19. Sixty subjects, 27 patients (15 women and 12 men) with long COVID and a mean age of 40.6 ± 13.4 years, were compared to 33 age-matched healthy controls (20 women and 13 men) with a mean age of 40.5 ± 9.8 years. Our data showed that patients with long COVID symptoms exhibited a significant decrease in odor threshold, odor discrimination, odor identification, and their sum TDI score compared to age-matched healthy controls. In addition, our results indicated significant correlations between odor discrimination and the increased activation in the right hemisphere, in the frontal pole, and in the superior frontal gyrus. This study indicated that the resting-state fMRI in combination with the objective evaluation of olfactory and gustatory function may be useful for the evaluation of patients with long COVID associated with anosmia and hyposmia.

Use of ozonated sunflower oil in the treatment of infectious endometritis in mares - Naiane F Oliveira; Camila S Ferreira; Luis F Silva; Isadora P Santos; Julio C Jacob; Bruno A Penna; Aline E Pinna (Journal of Equine Veterinary Science, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Implementation of IUCN criteria for the definition of the Red List of Ecosystems in Italy - G. Capotorti; L. Zavattero; R. Copiz; E. Del Vico; L. Facioni; S. Bonacquisti; R. Frondoni; M. Allegrezza; F. Attorre; G. Bacchetta; E. Barni; E. Biondi; et al. (Plant Biosystems, 2020)

A new anatomical interpretation for abaxialization in unifacial leaf blade of stone plants (Aizoaceae, Caryophyllales) - Aline S. Ogura; José Hernandes-Lopes; Gladys F. A. Melo-De-Pinna (Brazilian Journal of Botany, 2018)

Detectable cerebrospinal fluid JCV DNA in late-presenting HIV-positive patients: beyond progressive multifocal leukoencephalopathy? - S. Mornese Pinna; E. Scarvaglieri; M. G. Milia; D. Imperiale; V. Ghisetti; S. Audagnotto; A. Prochet; F. Lipani; S. Bonora; G. Di Perri; A Calcagno (Journal of NeuroVirology, 2017)

Monoterpenes from the essential oil from Brazilian propolis affect seedling cellular elongation - Marco A. S. Mayworm; Alex B. dos Santos; Gladys F. A. Melo-de-Pinna; Antonio Salatino; Maria L.F. Salatino; Diego Demarco (Brazilian Journal of Botany, 2017)

Conserving plant diversity in Europe: outcomes, criticisms and perspectives of the Habitats Directive application in Italy - G. Fenu; G. Bacchetta; V. Giacanelli; D. Gargano; C. Montagnani; S. Orsenigo; D. Cogoni; G. Rossi; F. Conti; A. Santangelo; M. S. Pinna; F. Bartolucci; et al. (Biodiversity and Conservation, 2017)

Comparative study of all Salmonella enterica serovar Enteritidis strains isolated from food and food animals in Greece from 2008 to 2010 with clinical isolates - T. Papadopoulos; E. Petridou; A. Zdragas; G. Mandilara; S. Nair; T. Peters; M. Chattaway; E. de Pinna; M. Passiotou; A. Vatopoulos (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Relationships between coastal sand dune properties and plant community distribution: The case of Is Arenas (Sardinia) - G. Fenu; D. Cogoni; C. Ferrara; M. S. Pinna; G. Bacchetta (Plant Biosystems, 2012)

Human impact on Paracentrotus lividus: the result of harvest restrictions and accessibility of locations - G. Ceccherelli; A. Pais; S. Pinna; N. Sechi; L. A. Chessa (Marine Biology, 2011)

Inhibition of protein kinase CK2 suppresses angiogenesis and hematopoietic stem cell recruitment to retinal neovascularization sites - A. A. Kramerov; M. Saghizadeh; S. Caballero; L. C. Shaw; S. Li Calzi; M. Bretner; M. Montenarh; L. A. Pinna; M. B. Grant; A. V. Ljubimov (Molecular and Cellular Biochemistry, 2008)

Taxonomic Impediment or Impediment to Taxonomy? A Commentary on Systematics and the Cybertaxonomic-Automation Paradigm - Marcelo R. de Carvalho; Flávio A. Bockmann; Dalton S. Amorim; Carlos Roberto F. Brandão; Mário de Vivo; José L. de Figueiredo; Heraldo A. Britski; Mário C. C. de Pinna; Naércio A. Menezes; Fernando P. L. Marques; Nelson Papavero; Eliana M. Cancello; et al. (Evolutionary Biology, 2007)

Intermittent Gastroesophageal Intussusception in a Dog: Clinical Features, Radiographic and Endoscopic Findings, and Surgical Management - M. Pietra; F. Gentilini; S. Pinna; F. Fracassi; A. Venturini; M. Cipone (Veterinary Research Communications, 2003)